Neuroinflammation alters GABAergic neurotransmission in hyperammonemia and hepatic encephalopathy, leading to motor incoordination. Mechanisms and therapeutic implications - Llansola, Marta; Arenas, Yaiza M.; Sancho-Alonso, María; Mincheva, Gergana; Palomares-Rodriguez, Andrea; Doverskog, Magnus; Izquierdo-Altarejos, Paula; Felipo, Vicente (Frontiers in Pharmacology, 2024)
Enhanced GABAergic neurotransmission contributes to impairment of motor coordination and gait and of cognitive function in different pathologies, including hyperammonemia and hepatic encephalopathy. Neuroinflammation is a main contributor to enhancement of GABAergic neurotransmission through increased activation of different pathways. For example, enhanced activation of the TNFα -TNFR1-NF-κB-glutaminase-GAT3 pathway and the TNFα-TNFR1-S1PR2-CCL2-BDNF-TrkB pathway in cerebellum of hyperammonemic rats enhances GABAergic neurotransmission. This is mediated by mechanisms affecting GABA synthesizing enzymes GAD67 and GAD65, total and extracellular GABA levels, membrane expression of GABAA receptor subunits, of GABA transporters GAT1 and GAT 3 and of chloride co-transporters. Reducing neuroinflammation reverses these changes, normalizes GABAergic neurotransmission and restores motor coordination. There is an interplay between GABAergic neurotransmission and neuroinflammation, which modulate each other and altogether modulate motor coordination and cognitive function. In this way, neuroinflammation may be also reduced by reducing GABAergic neurotransmission, which may also improve cognitive and motor function in pathologies associated to neuroinflammation and enhanced GABAergic neurotransmission such as hyperammonemia, hepatic encephalopathy or Parkinson's disease. This provides therapeutic targets that may be modulated to improve cognitive and motor function and other alterations such as fatigue in a wide range of pathologies. As a proof of concept it has been shown that antagonists of GABAA receptors such as bicuculline reduces neuroinflammation and improves cognitive and motor function impairment in rat models of hyperammonemia and hepatic encephalopathy. Antagonists of GABAA receptors are not ideal therapeutic tools because they can induce secondary effects. As a more effective treatment to reduce GABAergic neurotransmission new compounds modulating it by other mechanisms are being developed. Golexanolone reduces GABAergic neurotransmission by reducing the potentiation of GABAA receptor activation by neurosteroids such as allopregnanolone. Golexanolone reduces neuroinflammation and GABAergic neurotransmission in animal models of hyperammonemia, hepatic encephalopathy and cholestasis and this is associated with improvement of fatigue, cognitive impairment and motor incoordination. This type of compounds may be useful therapeutic tools to improve cognitive and motor function in different pathologies associated with neuroinflammation and increased GABAergic neurotransmission.